Spectral Properties of Anhydrous Carbonates and Nitrates. Issue 10 (26th October 2021) - Bishop, J. L.; King, S. J.; Lane, M. D.; Brown, A. J.; Lafuente, B.; Hiroi, T.; Roberts, R.; Swayze, G. A.; Lin, J.‐F.; Sánchez Román, M.
Abstract: The spectral properties of anhydrous carbonates and nitrates are dominated by strong, sharp vibrational bands due to the CO3 2− and NO3 − anions observed as absorption bands in near‐infrared spectra, as Reststrahlen features or absorption bands in mid‐IR spectra, depending on particle size, and as peaks in Raman spectra. These spectral features provide a reliable means to identify the occurrence of carbonates and nitrates on planetary surfaces, which in turn contribute to our understanding of the environment and chemistry of planetary bodies. Four modes occur for carbonates and nitrates due to symmetric stretching ( ν 1 ), out‐of‐plane bending ( ν 2 ), asymmetric stretching ( ν 3 ), and in‐plane bending ( ν 4 ). The vibrational absorptions of these spectral features vary with the mineral structure and the size of the cation, where the calcite‐, dolomite‐, aragonite‐, and alkali‐type structures result in different spectral features. Mid‐IR bands for carbonates and nitrates occur from 1, 040 to 1, 105 cm −1 for ν 1, from 810 to 906 cm −1 for ν 2, from 1, 275 to 1, 590 cm −1 for ν 3, and from 670 to 756 cm −1 for ν 4 . In Raman spectra the carbonate and nitrate absorptions are observed near 1, 050–1, 080 cm −1 for ν 1, near 880 cm −1 for ν 2, near 1, 415–1, 430 cm −1 for ν 3, and near 680–700 cm −1 for ν 4 . NIR spectra include bands due to overtones and combinations at ∼1.75, 1.9, 2.0, 2.3, 2.5, 3.4, 4.0, and 4.6 μm for carbonates and ∼1.8, 2.0, 2.2, 2.4, 2.6, 3.5, 4.1, and 4.8 μm for nitrates. This study provides data for remote determination of carbonate and nitrate chemistry and will enable better characterization of these minerals on planetary bodies including Mars, Ceres, and Bennu. Plain Language Summary: Carbonates are widespread minerals on Earth and have been identified as well on Mars, Ceres, near Earth asteroid (101955) Bennu, and in carbonaceous meteorites. Understanding the spectral properties of carbonates enables detection and characterization of this important mineral group. Furthermore, identifying the specific type of carbonate on planetary surfaces can help us constrain the geochemical environment of these planets or bodies. The spectral properties of nitrates are presented here as well because nitrates exhibit similar spectral features to carbonates due to their similar mineral structures. Nitrates are yet to be detected on planets other than Earth, but nitrogen has been detected on bodies in our Solar System and nitrates may be detected once researchers have access to their spectral properties. Key Points: Spectral bands are presented for remote detection of anhydrous carbonates and nitrates Mid‐IR band center comparisons for the ν 3 vibration compared to the ν 2 and ν 4 vibrations enable identification of carbonate chemistry NIR band center comparisons for ∼2.3 versus 2.5 μm, ∼2.3 versus 4 μm, and ∼3.4 versus 4 μm best enable identification of carbonate chemistry